Conditions for maximizing the gains from a Western Hemisphere Free Trade Agreement - Krueger, Anne O. (IDB WashingtonUS, 1992)
Asseses the possibilities and the dangers in participating in a Western Hemisphere Free Trade Agreement. Considers the sorts of policies that Latin American countries could adopt which would provide the maximum scope for gains under such an Agreement.